Educational robot for the care of infectious diseases in children: A review of the scientific literature 2010 - 2020 - Cabanillas-Carbonell, Michael (2021)
ABSTRACT Due to the pandemic caused by the COVID-19, we are forced to maintain a social distance, relying on technology such as the use of robots for both commercial and educational activities. This document is a systematic review of scientific literature using Prism methodology and aims to determine the best characteristics for the development of educational robots in children on infectious disease care. We obtained 50 articles associated to the research topic collected from databases such as IEEE Xplore, Scielo, Scopus and WoS. The results were synthesized in different tables and graphs separated in approaches of: robotics in education, robotics in relation to humans, education in diseases, robotics in health and digital applications in education, where the first one is the most treated in the articles found.